Efeitos das diferentes montagens da estimula????o transcraniana por corrente cont??nua na funcionalidade de crian??as com paralisia cerebral: ensaio cl??nico aleatorizado, placebo-controlado e duplo cego - Duarte, Nat??lia de Almeida Carvalho (2017)
Objective: To verify the effects of different montages of transcranial direct current stimulation (tDCS) over the primary motor cortex associated with treadmill training on the functionality of children with spastic hemiparetic CP. Material and Method: Thirty children with spastic hemiparesis, aged 5 to 12 years, were randomly allocated into three groups: Group 1: anodic tDCS over the primary motor cortex (M1) and cathode over the contralateral supraorbital region associated with Treadmill training; Group 2: anodic sham tDCS over the M1 and cathode over the contralateral supra-orbital region associated with treadmill training; Group 3: Anodal tDCS over M1 of the injured hemisphere and cathodal stimulation in contralateral M1 associated with treadmill training. The evaluation (before, after and one month after the protocol) consisted of three-dimensional gait analysis, static balance, functional balance, functional performance, quality of life and electromyography of the lower limbs. The protocols were performed for two consecutive weeks, with five training sessions per week and duration of 20 minutes per session. Transcranial stimulation was performed simultaneously with treadmill training with an intensity of 1 mA. The results were statistically analyzed assuming a level of significance of 0.05 (p <0.05). Results: Study I published on Journal of Motor behavior. There is an adaptation in the geometry of motor areas and that the cortical representation of movement is variable following a brain lesion. The 10-20 EEG system may not be the best option for locating the primary motor cortex and position the electrodes for noninvasive brain stimulation in children with cerebral palsy. Study II: Protocol study accepted for publication on Pediatric Physical therapy journal. Study III: Submitted to Brain Stimulation Journal. It was observed that when the effects obtained by different unilateral and bilateral FETC assemblies in the pediatric population of spastic hemiparetic CP, the unilateral active assembly showed a slight improvement in the results when compared to the other groups. It was also observed that when compared to the effects obtained by different unilateral active assembly showed an improvement in the mean velocity of oscillation of the COP in the lateral-lateral sense when compared to the other groups (p <0.05). Regarding the functional scales, the unilateral assembly presented better results in the timed up and go test and in the pediatric disability assessment inventory. Bilateral assembly generated better results on the pediatric balance scale, both groups showing improved quality of life.Conclusion: It was observed that both unilateral and bilateral assemblies may offer functional benefits to the pediatric population with spastic hemiparetic cerebral palsy, with a slight superiority of unilateral assembly effects compared to bilateral and placebo assembly.